Pengaruh Risiko ESG terhadap Nilai Perusahaan dengan Kepemilikan Institusional sebagai Variabel Moderasi - Nabit, Muhammad; Helmy, Herlina (Jurnal Nuansa Karya Akuntansi, 2025)
Climate change poses a serious challenge to human survival, the global economy, and companies, especially in developing countries with vulnerable infrastructure. This condition raises awareness of the importance of managing environmental risks through the implementation of ESG. ESG is needed to improve corporate transparency, responsibility, and sustainability, while helping companies adapt to increasingly pressing environmental and social challenges. This study aims to empirically test the effect of environmental, social, and governance risks on company value with institutional ownership as a moderating variable. This study uses moderated regression analysis to test the formulated hypotheses. The population in this study were all companies listed on the Indonesia Stock Exchange in 2023. Using the purposive sampling method, 74 companies were selected as research samples for the one-year observation period of 2023. Company Value as the dependent variable is measured by Tobin's Q. ESG risk as an independent variable uses a score issued by Morningstar Sustainalytics. Institutional Ownership can be measured by the number of shares owned by institutions with the number of shares outstanding. The results of the study indicate that the ESG risk of companies listed on the Indonesia Stock Exchange does not significantly affect the company's value. Further results, this study found that institutional ownership is able to negatively moderate or weaken the relationship between ESG risk and company value. These findings provide new insights into the relationship between ESG risk, company value, and institutional ownership in the context of the Indonesian capital market and corporate sustainability.